Синтез и биологические свойства амидов 1,4-бензодиоксан-2-алканкарбоновых кислот - С. О. Вартанян; А. С. Авакян; А. Б. Саргсян; С. А. Арутюнян; А. С. Цатинян; А. С. Григорян; Г. В. Гаспарян (ՀՀ ԳԱԱ հրատ.)
Реакцией хлорангидридов 1,4-бензодиоксан-2-уксусной и 1,4-бензодиоксан-2-пропионо-вой кислот с разнообразными замещенными арил-, арилалкил- и гетериламинами получен ряд новых амидов, содержащих соответствующие фармакофорные фрагменты. Изучены их анти-гипоксические, симпато- и адренолитические свойства, а также антимоноаминоксидазная активность. 1,4-Բենզոդիօքսան-2-քացախաթթվի և 1,4-բենզոդիօքսան-2-պրոպիոնաթթվի քլոր-անհիդրիդների և զանազան տեղակալված արիլ-, արիլալկիլ- և հետերիլամինների փոխազդեցությամբ սինթեզվել են համապատասխան ամիդային միացություններ: Ուսումնասիրվել են նրանց հակահիպօքսիկ, ինչպես նաև սիմպատո- և ադրենոլիտիկ հատկությունները: Հետազոտվել է սինթեզված ամիդների հակամոնոամինօքսիդազային ակտիվությունը: By condensation of chloranhydrides of 1,4-benzodioxane-2-acetic and 1,4-benzodioxane-2-propionic acides with substituted aryl-, arylalkyl- and heterylamines a series of different new amide derivatives of 1,4-benzodioxane have been synthesized. The structures of these compounds have been established by IR and H1NMR methods. The sympatho- and adrenolytic properties of synthesized compounds have been investigated. It was shown also, that the antihypoxic activity of amides of 1,4-benzodioxan-2-ylpropionic acid was higher, than amides of 1,4-benzodioxan-2-yl-acetic acid. Some of these compounds have been screened for their antimonoaminoxidase activity and it was found, that the amides of 1,4-benzodioxan-2-ylpropionic acid with pyridine fragment displayed moderate activity.
Keywords: Biochemistry; Organic Chemistry